Knockdown of hsa_circ_0102231 Impedes the Progression of Liver Cancer through the miR-873–SOX4 Axis - Qian, Jingyu; Jiang, Banghong; Qin, Zhongqiang; Tan, Yulin (Current Gene Therapy, 2025)
BackgroundHepatocellular carcinoma (HCC) is one of the most intractable tumors in the world due to its high rate of recurrence and heterogeneity.AimsThe objective of this study was to investigate the role of circular RNA 0102231 (hsa_circ_0102231) in the progression of liver cancer.MethodsIn this study, quantitative polymerase chain reaction experiments were performed to quantify the hsa_circ_0102231 level in different liver cancer cell lines. Bioinformatics analysis, as well as a dual-luciferase reporter and RNA pull-down assay, were used to identify putative hsa_circ_0102231 downstream targets. Colony formation and CCK8 assays were utilized to examine cell proliferation, whereas Transwell assays were employed to monitor cell migration. Lastly, the role of hsa_circ_0102231 in liver cancer was assessed in a subcutaneous xenograft model.ResultsThe expression of hsa_circ_0102231 increased significantly in HepG2 and Huh-7 cells compared with controls, and hsa_circ_0102231 knockdown inhibited cell proliferation and migration in vitro and in vivo. Bioinformatics analysis, as well as a dual-luciferase reporter and RNA pulldown assay, revealed that miR-873 and SOX4 were hsa_circ_0102231 downstream targets. miR-873 inhibition or SOX4 overexpression rescued the proliferation and migration of HepG2 and Huh-7 cells after hsa_circ_0102231 knockdown. Furthermore, SOX4 overexpression reversed the miR-873-induced inhibition of cell migration and proliferation in vitro.ConclusionThese results show that hsa_circ_0102231 knockdown impedes the progression of liver cancer by regulating the miR-873/SOX4 axis. However, further studies are needed to determine whether hsa_circ_0102231 may be a therapeutic target in liver cancer.
Keywords: cell migration